Characteristics of aortic root and vascular anatomy in bicuspid versus tricuspid aortic valve stenosis in patients undergoing transcatheter aortic valve implantation. (25th November 2020) - Arow, Z; Yaron, A; Nassar, M; Perlman, G; Lessick, J; Brodov, Y; Vaknin-Assa, H; Steinvil, A; Kornowski, R; Hamdan, A
Abstract: Background: Transcatheter aortic valve implantation (TAVI) is being increasingly performed in patients with bicuspid aortic valve stenosis (AS). Objectives: This study sought to compare aortic root and ilio-femoral artery characteristics and clinical outcomes in patients with bicuspid versus tricuspid AS from the Bicuspid AS TAVI multicenter registry. Methods: 88 patients with bicuspid AS and 213 matched patients with tricuspid AS were referred for pre-procedural computed tomography (CT) evaluation before TAVI. We performed a detailed assessment of aortic root anatomy: size of the annulus, sinus of Valsalva (SoV), sino-tubular junction (STJ); we also determined the dimensions of aorta, left subclavian, and ilio-femoral arteries. Results: Patients with bicuspid AS had significantly larger aortic root dimensions, (annulus mean diameter: 25.5±2.9 mm vs. 23.7±2.4 mm, SoV mean diameter: 35.3±4.7 mm vs. 32±4.4mm, STJ mean diameter: 31.5±4.9 mm vs. 27.6±3.5 mm; respectively) than patients with tricuspid AS (P value for all <0.001), even after adjustment for their larger BSA and height. Dimensions of ascending aorta, left subclavian artery, and ilio-femoral arteries were also consistently larger in bicuspid than in tricuspid AS morphology. Conclusions: Patients with bicuspid AS had significantly larger aortic root dimensions, larger ascending aorta, subclavian artery and ilio-femoral arteries even after adjustment for their BSA and height. Funding Acknowledgement: Type of funding source: Public hospital(s). Main funding source(s): Rabin Medical Center